DDT degradation efficiency and ecotoxicological effects of two types of nano-sized zero-valent iron (nZVI) in water and soil - El-Temsah, Yehia S; Sevcu, Alena; Bobcikova, Katerina; Cernik, Miroslav; Joner, Erik J (Chemosphere, 2016)
Nano-scale zero-valent iron (nZVI) has been conceived for cost-efficient degradation of chlorinated pollutants in soil as an alternative to e.g permeable reactive barriers or excavation. Little is however known about its efficiency in degradation of the ubiquitous environmental pollutant DDT and its secondary effects on organisms. Here, two types of nZVI (type B made using precipitation with borohydride, and type T produced by gas phase reduction of iron oxides under H2) were compared for efficiency in degradation of DDT in water and in a historically (>45 years) contaminated soil (24 mg kg(-1) DDT). Further, the ecotoxicity of soil and water was tested on plants (barley and flax), earthworms (Eisenia fetida), ostracods (Heterocypris incongruens), and bacteria (Escherichia coli). Both types of nZVI effectively degraded DDT in water, but showed lower degradation of aged DDT in soil. Both types of nZVI had negative impact on the tested organisms, with nZVI-T giving least adverse effects. Negative effects were mostly due to oxidation of nZVI, resulting in O2 consumption and excess Fe(II) in water and soil.
Keywords: ekotoxikologie; látky znečišťující půdu; len; Nanoparticles; Environmental Restoration and Remediation; železo; Hordeum; chemické látky znečišťující vodu; půda; Flax; Soil Pollutants; ječmen (rod); Iron; kyslík; Oligochaeta; Water Pollutants, Chemical; Escherichia coli; korýši; zvířata; Soil; Crustacea; DDT; Nano-remediation; regenerace a remediace životního prostředí; Aged pollutants; Oxygen; Ecotoxicology; Chlorinated organic pollutants; Animals